Malaysia Towards Cashless Society - Kadar H.H.B.; Sameon S.S.B.; Din M.B.M.; Rafee P.A.B.A. (Springer Verlag, 2023)
Developing countries; Benefits; Cashless; Drawbacks; Malaysia; Society; Industry 4.0